Pengembangan Perangkat Pembelajaran Tematik SD Kelas IV - Faeza Rezi S; Andriyas Hariyandi; Wira Buana (Universitas Putra Indonesia YPTK Padang, 2022)
The thematic learning model has a scientific approach that is essentially a scientific approach where the learning process will be more meaningful if the child experiences what he is learning. The implementation of the elementary thematic learning curriculum is a tendency to return to the initial thought that students will learn better when the environment is created naturally. Teachers must place students as the center of all learning activities so that they are able to explore material and enrich their learning experiences. Thus a thematic learning tool for SD Class IV is designed as a guide for teachers and students to learn based on a thematic curriculum. This research is a type of research and development that aims to measure the validity, practicality and effectiveness of developing thematic learning devices for Class IV SD. The research and development model used is 4-D (four D Models). This model consists of 4 stages, namely define, design, develop, and disseminate. The test subjects in this development research were 5 teachers at SDN 03 Alai Padang, 2 teachers at SDN Experiment Padang and 30 students in grade IV.b at SDN 03 Alai Padang. Based on the results of the validity test conducted by the expert, the development of thematic learning tools for SD class IV obtained an overall average of 87.16% which is in the very valid criteria. The practicality test result is 93.37% which is in the very practical criteria. Furthermore, the effectiveness test can be seen from the results of student learning before (pre-test) and after (post-test) trials at 3.86% which are at an effective level for use